Oedipus and the Devil : witchcraft, sexuality, and religion in early modern Europe - Roper, Lyndal (Routledge, 1994)
This bold and imaginative book marks out a different route towards understanding the body, and its relationship to culture and subjectivity. Amongst other subjects, Lyndal Roper deals with the nature of masculinity and feminity.